(untitled) (Indian Journal of Nematology, 2024)
The present investigations were carried out to manage root-knot nematode, Meloidogyne incognita on coriander and fenugreek under screen-house conditions. Organic cakes such as castor, mustard and neem cake were used at two doses, i.e., 10 and 15 g/kg soil. All the organic cakes effectively reduced nematode multiplication and enhanced plant growth parameters, viz., shoot length, root length, shoot weight (fresh and dry), root weight (fresh and dry) and the number of branches per plant. Among the treatments, mustard cake @ 10 g/kg soil was most effective in managing the nematode population and increasing the growth parameters of plants, followed by neem cake @ 15 g/kg soil in both coriander and fenugreek.